Strategy for Prevention and Quality Improvement of Urban Slumps Based on Community Empowerment - Sulsalman Moita; Darmin Tuwu; Allan Darmawan (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
The purpose of this study was to examine the characteristics of slum areas and to analyze strategies for preventing and improving the quality of community empowerment-based slum settlements in Langara City, Konawe Islands Regency. This research method is descriptive qualitative with a case study approach, while the research informants are individuals and groups who are involved in the slum prevention and quality improvement program. The data were collected using in-depth interviews, observation, and document studies, while the data analysis techniques were carried out qualitatively. The results show that the indicators of a slum in Langara City are: the condition and quality of houses are generally less regular, dense, with minimal air and light circulation, environmental sanitation is not supported by wastewater disposal, access to settlements is relatively good, the garbage disposal system is not supported by landfills. Finally, limited distribution of net water, and the unavailability of fire protection. Furthermore, the strategy for preventing and improving the quality of slum based on community empowerment shows 1) slum prevention strategies with indicators: the high rate of community participation in attending counseling on the importance of maintaining environmental health and the high involvement of residents in preventing slums through cooperation, community service, and helping out; 2) slum quality improvement strategy with indicators: high capacity and community involvement in the renovation and restoration of slum shelters; and the low level of public awareness of joining the relocation program in slum pockets.